A Brief Review of the Synthesis and Catalytic Applications of Graphene‐Coated Oxides. Issue 13 (5th June 2017) - Luo, Wen; Zafeiratos, Spyridon
Abstract: The potential applications of graphene‐based materials in catalysis have been intensively studied owing to the unique 2D structure of graphene and its superior physicochemical properties. Recently, graphene‐coated oxide composites have been fabricated and tested as catalysts or catalytic supports, demonstrating a significant improvement on the catalytic performance. This article briefly reviews the recent progress in the design and fabrication of graphene‐coated oxides including wet transfer, chemical vapor deposition and self‐assembly methods. The applications of these materials in catalysis as well as the role of graphene in the modification of oxide properties and the enhancement of catalytic activity are also discussed. Abstract : Graphene coated oxides are a significant platform for both fundamental studies and applications in catalysis. The latest advances in the synthesis and applications of graphene‐coated oxides are reviewed. The challenges in the future studies are also discussed.